2007
DOI: 10.1007/s11160-007-9064-8
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxins in aquatic species: metabolism, toxicity and perspectives

Abstract: Among all known mycotoxins, aflatoxins represent the most investigated, widespread and worrisome source of contamination of foods and feed worldwide. In the early 1960s, soon after the finding of aflatoxin B 1 (AFB 1 ) in the feedstuffs of aquacultured rainbow trout that had died in an epizootic of hepatomas, great scientific discoveries were made in several areas by a number of researchers under the direction of scientists like J. Halver, R. 0. Sinnhuber, G. S. Bailey, J. D. Hendricks and colleagues. Since th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
125
1
34

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 157 publications
(163 citation statements)
references
References 178 publications
3
125
1
34
Order By: Relevance
“…For example, rainbow trout is considered very susceptible to AFB1 [4,8]. The first documented incidences of aflatoxicosis affecting fish health occurred in the 1960s in trout hatcheries.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, rainbow trout is considered very susceptible to AFB1 [4,8]. The first documented incidences of aflatoxicosis affecting fish health occurred in the 1960s in trout hatcheries.…”
Section: Discussionmentioning
confidence: 99%
“…Although cottonseed meal is no longer used as a major ingredient in feed formulations, poor storage of other feed ingredients and nutritionally complete feeds can lead to contamination with aflatoxins [29,30]. Santacroce et al [8] explained that dosages of 0.5-1 AFB1 mg/kg feed resulted in 50% mortality. Other study showed that levels of 0.02 AFB1 mg /kg feed produced 96% incidence of liver tumors in rainbow trout.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations